Effects of Aroclor 1254 on Intestinal Immunity, Metabolism, and Microflora in Zebrafish - Zhu, Di-Hua; Nie, Fang-Hong; Zhang, Min; Wei, Wan; Song, Qing-Lang; Hu, Yao; Kang, Dan-Ju; Chen, Zhi-Bao; Lin, Hong-Ying; Chen, Jin-Jun (Frontiers in Nutrition, 2022)
Polychlorinated biphenyls (PCBs) are widely distributed environmental toxicants, whose biological toxicity is magnified step by step through the transmission of the food chain. However, there is little research about the effect of PCBs on intestinal epithelial barrier function. In this experiment, the effects of PCB exposure on the intestines of zebrafish were evaluated. Animals were exposed to Aroclor 1254 (5 μg/L, 10 μg/L, 15 μg/L). After 21 days, the changes in histology, enzyme biomarkers, intestinal microorganisms, and metabolomics were detected. The inflammation and oxidative stress in the intestines of zebrafish were observed. Additionally, there were significant changes in intestinal microbiota and tissue metabolism, most of which were associated with oxidative stress, inflammation, and lipid metabolism. The results showed that PCBs exposure resulted in intestinal inflammation and oxidative stress in zebrafish.Moreover, intestinal metabolites and intestinal microflora of zebrafish were also disturbed. This study verified that exposure can lead to intestinal damage and changes in intestinal metabolic capacity and microorganisms, enlightening the consequences of PCB exposure.